Small hive beetle [SHB], Aethina tumida - KOKKINIS (M. Ι. ΚΟΚΚΙΝΗΣ) M. I. (Journal of the Hellenic Veterinary Medical Society, 2017)
Small hive beetle [SHB], Aethina tumida, is a honeybee parasite native to Africa, where it is only a minor pest of the African subspecies damaging weak or stressed colonies, abandoned honeybee nests and stored bee products. In contrast, it can be a harmful parasite of European honeybee A. meìlifera. In this paper, the literature concerning morphology, biology, longevity and reproductive success of SHB, as well as host-parasite relationships, are reviewed. Distribution, potential damages to colonies, stored honey and equipment, as well as the economic importance of beede infestations, are presented. Moreover, diagnosis methods, control methods and strategies are also reviewed.